Peningkatan Keaktifan Siswa melalui Metode Diskusi pada Pembelajaran Ilmu Pengetahuan Alam dan Sosial di Madrasah Ibtidaiyah - Ulfy Rohmawati; Mahluddin Mahluddin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The purpose of this research is to promote the active engagement of fourth-grade students at Madrasah Ibtidaiyah Negeri (MIN) 4 Muaro Jambi in Natural and Social Sciences (IPAS) learning by using the discussion approach. The key issue addressed in this research is a low degree of student participation, as shown by their lack of bravery to ask and answer questions, as well as restricted contact throughout the learning process. This research adopts a Classroom Action Research (PTK) technique based on the Kemmis and McTaggart model, with two cycles of preparation, action, observation, and reflection phases. The study included 27 pupils from Class IV A. Data collecting methods included observations, interviews, testing, and documentation. The study findings revealed a considerable increase in learning activities. In the first cycle, average student engagement varied between 52% and 56%, whereas in the second cycle, it jumped dramatically to 81% to 89%. This enhancement also had an influence on learning outcomes, as the class average score increased from 67 to 71, and the classical completion rate increased from 63% to 89%, surpassing the minimal criterion stipulated by the Learning Objective Completion Criteria (KKTP). As a result, it is possible to infer that using good conversation approaches improves student engagement and learning results in IPAS learning.